Uncovering decolonial pedagogies for learning agroecological transitions: comparative analysis of South America cases - Bonatti, Michelle; Reynaldo, Renata Guimarães; Martín-López, Berta; Bolivar, Sergio; Cordero-Fernández, María; Miguel, Giovanna Chavez; Martin, Adriana; Hämmerle, Janika; Schröter, Barbara; Erismann, Carla; da Silva Rosa, Teresa; Hellin, Jon; et al. (Elsevier, 2025)
Agroecological transitions represent strategic pathways for transforming agricultural systems to meet urgent global sustainability goals. These transitions encompass fundamental changes in social-ecological relationships, knowledge systems, and power dynamics within food systems. However, the mechanisms facilitating such transitions remain insufficiently understood, particularly regarding the diversity and efficacy of pedagogical models employed in existing agroecological initiatives. This knowledge gap is especially pronounced within Global South contexts, especially Latin America, where decolonial approaches hold particular relevance and tradition within effective agroecology initiatives. Using a decolonial lens, this study explores the pedagogical models used in community-led agroecological initiatives in Brazil, Colombia, and Peru. Drawing on semi-structured interviews and workshops (n 140), alongside participant observations, we applied a qualitative archetypes analysis to examine three community-led agroecology initiatives. We identified three distinct but interconnected contextual narratives: a. Living Pedagogies; b. Resistance Pedagogies; and c. Hybrid Pedagogies. Despite these different contextual narratives, they share clear patterns, which allowed us to identify one major archetype − the South pedagogies archetype. The decolonial pedagogy found can be fundamental to accelerate agroecological transitions. Traditional communities in Colombia and Peru have preserved and evolved their agroecology knowledge systems through generations of collective learning, offering profound insights into sustainable food production that transcend the limitations of Western scientific methodologies. In parallel, decolonial pedagogies in the Brazilian case were essential to promote urban agroecological transition that started during the 2000s. These findings inform agroecological transition development based on learning processes that value multiple ways of being.